CONSTRAINTS OF ORGANIC FARMING TECHNOLOGY AMONG SMALL- SCALE VEGETABLE FARMERS IN SOUTH-SOUTH ZONE OF NIGERIA - Okonkwo-Emegha, K.; Okafor, I. P.; Isibor, C. A. (Journal of Agripreneurship and Sustainable Development, 2020)
The survey examined constraints of organic farming technologies among small-scale vegetable farmers in South-South zone of Nigeria. A multistage sampling technique was employed to select the study location and respondents. Data were collected from 480 small-scale organic vegetable farmers using structured questionnaire. Data obtained was analyzed using descriptive statistics. The results revealed that majority (93.00%) of organic fluted pumpkin farmers were challenged with inadequate finance, 92.80% were faced with shortage of organic materials, 86.10% with poor awareness, 72.40% faced poor market access and slightly more than half (51.10%) were constrained with poor willingness to pay for the material. It was concluded that the most serious constraints to organic fluted pumpkin production in the study area were inadequate finance, shortage of organic materials, poor awareness, poor market and poor willingness to pay for the material. The study therefore, recommended that cheap loans should be granted to organic fluted pumpkin farmers by the cooperative societies and bank of Agriculture (BOA) through adequate Government policy interventions to allow improvement in their productivity, profit, and ensure enterprise sustainability.